ANALISIS PENGARUH CASH CONVERTION CYCLE, AVERAGE COLLECTION PERIOD, INVENTORY COLLECTION PERIOD, AVERAGE PAYMENT PERIOD DAN CURRENT RATIO TERHADAP PROFITABILIITAS (Studi Empiris Pada Sektor Industri Barang Konsumsi BEI Pada Tahun 2013-2017) - Rosyid, Sholeh Fauzan; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2019)
The purpose of this study was to determine the effect of working capital management (Cash Convertion Cycle (CCC), Average Collection Period (ACP), Inventory Collection Period (ICP) Average Payment Period (APP) and Current Ratio (CR) to profitability of Go Public consumer goods company. Profitability is proxied by ROA as a measure of the size of profit that produced.The sample in this study is a sector of consumer goods company that listed on the IDX (Indonesia Stock Exchange) during the period 2013-2017. The number of samples were 35 company taken by purposive sampling method. The analytical method of this study uses multiple linear regression with the SPSS 25 program which has previously passed the classic assumption test.The results of this study indicate that Cash Convertion Cycle (CCC), Average Collection Period (ACP) and Inventory Collection Period (ICP) had negative and significant effect on ROA. Current Ratio (CR) has positive and significant effect on ROA. While the Average Payment Period (APP) has an insignificant positive effect on ROA.